2019
DOI: 10.1038/s41586-019-1787-x
|View full text |Cite
|
Sign up to set email alerts
|

Distributed coding of choice, action and engagement across the mouse brain

Abstract: Vision, choice, action, and behavioral engagement arise from neuronal activity that may be distributed across brain regions. Here we delineate the spatial distribution of neurons underlying these processes. We used Neuropixels probes 1,2 to record from ~30,000 neurons in 42 brain regions of mice performing a visual discrimination task 3. Neurons in nearly all regions responded non-specifically when the mouse initiated an action. By contrast, neurons encoding visual stimuli and upcoming choices occupied restric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
713
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 623 publications
(869 citation statements)
references
References 59 publications
71
713
2
Order By: Relevance
“…Interpretation of neural activity in terms of neural circuits relies on accurate localization of individual electrodes and thereby the recorded neurons. Several workflows have been described (Allen et al, 2019;Siegle et al, 2019;Steinmetz et al, 2019), but groundtruth experiments assessing the accuracy of electrode localization are lacking. We took advantage of the ChR2-EYFP in bundles of axons and compared the locations of ChR2-EYFP expression as judged by fluorescence with light-evoked activity measured with electrodes that were registered to the CCF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretation of neural activity in terms of neural circuits relies on accurate localization of individual electrodes and thereby the recorded neurons. Several workflows have been described (Allen et al, 2019;Siegle et al, 2019;Steinmetz et al, 2019), but groundtruth experiments assessing the accuracy of electrode localization are lacking. We took advantage of the ChR2-EYFP in bundles of axons and compared the locations of ChR2-EYFP expression as judged by fluorescence with light-evoked activity measured with electrodes that were registered to the CCF.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Neuropixels probes (Jun et al, 2017a) have 960 recording electrodes distributed over 9.6 mm shanks. Because of their length, Neuropixels recordings in rodents naturally span multiple brain areas (Allen et al, 2019;Jun et al, 2017a;Steinmetz et al, 2019). Neuropixels probes do not have the electronic circuits to pass the large currents that are required to produce electrolytic lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of four cortical areas (dmFrC, dlFrC, M1, and S1b) was bilaterally photoinhibited in randomly chosen half of the trials. However, the effect of learning on the convergence of the cortex-wide activity could also be explained by the licking behavior because its trial-by-trial variability also decreased as the learning progressed ( Figure 1E), and such movements can have a large effect on the neuronal activity as a whole (Musall et al, 2019;Steinmetz et al, 2019;Stringer et al, 2019). Therefore, we compared the trial-by-trial correlation of the lick-rate and the trial-by-trial correlation of the neuronal trajectories in each learning stage and CS presentation, and found that these correlations showed a strong association ( Figure S2F).…”
Section: Cortex-wide Neuronal Activity and Licking Are Highly Synchromentioning
confidence: 99%
“…However, we have also provided ONE light (see Appendix 2), a backend that allows scientists to share data using ONE by simply uploading files to a web server, or to figshare . The ONE system is extensible, allowing users to add non-standard data sets using their own namespace, and, for example, has been used to share large-scale electrophysiology recordings collected in a different task via figshare file upload 13 . Full details of the ONE protocol are given in Appendix 1.…”
Section: Datajoint Joblib Daskmentioning
confidence: 99%